Microstructure of confectionery masses revealed by cryo-planing - Nijsse, Jaap; Cruz Serna, Adriana Fernanda; Melnikov, Sergey M. (Frontiers in Food Science and Technology, 2024)
Here we present a novel, combined cryo-scanning electron microscopy (cryo-SEM) and confocal laser scanning microscopy (CLSM) method for imaging of chocolate confectionery product microstructures of several millimeters down to about 100 nm. The SEM part of the method is based on cryo-fixation, cryo-polishing, and scanning electron microscopy, at low vacuum and low temperature using the backscattered electron signal. Starting with cryo-fixation of the chocolate sample in a desired state (cooled, ambient, or melted), the sample is cryo-planed in a cryo-ultramicrotome. Once a polished cut is obtained, the sample is analyzed using a cryo-SEM technique, with the unusual combination of low temperature and low vacuum settings, without heavy metal coating. Imaging is done based on material density contrast. Elemental composition of particles is recorded by energy dispersive x-ray spectroscopy (EDS). The combination of imaging contrast and EDS allows identification and measurement of the four main constituents of chocolate (cocoa solids, fat, sugar, and milk solids). Finally, the same cryo-polished sample sections of solid chocolate products are analyzed using a CLSM imaging technique to reveal complementary microstructural details. An obvious application of the method could be the visualization and quantitative analysis of the size, shape, and composition of chocolate confectionery products.